DEVELOPING MULTIMEDIA SUPPORTED CRITICAL THINKING TEST on HEAT TRANSFER CONCEPT - Mahbubah, Khoiro; Hermita, Neni (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Critical thinking skill is one of the skills that should be possessed by the students to compete in the global area. There are many ways to practice and increase critical thinking skills of the students by using model and media learning. In order to measure critical thinking skills of the students appropriately, we need the precise test instrument. The purposes of this research are to develop and validate of Multimedia Supported Critical Thinking Test (MSCiT Test) instrument in heat transfer learning material for senior high school students. MSCiT Test is a test instrument that optimizes the function of computer by presenting media, simulation, video, and picture which describe the test that will be done by the students in an interactive dynamic content, a content that enables the students to feel as if they face the real phenomena in the test. MSCiT Test is adapted Halpern’s critical thinking framework which was developed by Tiruneh, involving four different categories, reasoning, hypothesis testing, argument analysis and problem solving and decision making. The research method employed in this research was the research and developmental 4-D model method adapted from Thiagarajan, involving four main steps, define, design and develop. MSCiT Test has been tested in terms of its validity. The validity test consists of construct,the analysis of construct validity was conducted by using Content Validity Ratio (CVR). And the result of value of CVR all of item in instrument are valid with value of CVR 0.722.